Cullin 5 is a novel candidate tumor suppressor in renal cell carcinoma involved in the maintenance of genome stability - Tapia-Laliena, María Angeles; Korzeniewski, Nina; Peña-Llopis, Samuel; Scholl, Claudia; Fröhling, Stefan; Hohenfellner, Markus; Duensing, Anette; Duensing, Stefan (Oncogenesis, 2019)
Clear cell renal cell carcinoma (ccRCC) is intimately associated with defects in ubiquitin-mediated protein degradation. Herein, we report that deficiency in the E3 ligase subunit cullin 5 (CUL5) promotes chromosomal instability and is an independent negative prognostic factor in ccRCC. CUL5 was initially identified in an RNA interference screen as a novel regulator of centrosome duplication control. We found that depletion of CUL5 rapidly promotes centriole overduplication and mitotic errors. Downregulation of CUL5 also caused an increase of DNA damage that was found to involve impaired DNA double-strand break repair. Using immunohistochemistry, CUL5 protein expression was found to be below detection level in the majority of RCCs. A re-analysis of the TCGA ccRCC cohort showed that a reduced CUL5 gene expression or CUL5 deletion were associated with a significantly worse overall patient survival. In conclusion, our results indicate that CUL5 functions as a novel tumor suppressor with prognostic relevance in ccRCC and is critically involved in the maintenance of genome stability.